Pengaruh Keaktifan Mahasiswa Berorganisasi dan Motivasi Belajar Terhadap Prestasi Belajar (Studi Pada Himpunan Mahasiswa Jurusan Angkatan 2016-2017 Fakultas Ekonomi Dan Bisnis Universitas Tanjungpura) - YOVE, RUDNI B1021161029 (Jurnal Manajemen Update, 2020)
ABSTRACTThis study aims to discuss and analyze the effect of student’s activeness on organization and learning motivation toward learning achievement (study on department student association batch 2016-2017 in Faculty of Economic and Business Tanjungpura University). The population in this study ware 178 students batch 2016-2017 who joined the department student association. The sample in this study is 124 students who joined the department student association using probability sampling technique. The data used is analysis multiple regression.The result of this study indicate that: (1) Students activeness on organization have a positive and significant effect on learning achievemet student who joined the department student association batch 2016-2017 (2) Learning motivation has a positive and significant effect on learning achievemet student who joined the department student association batch 2016-2017 (3) There is a simultaneous effect between students activeness on organization and learning motivation on learning achievemet student who joined the department student association batch 2016-2017. Keywords: Student’s Activeness on Organization, Learning Motivation, and Learning Achievement.Daftar Pustaka Rahman, A & Ali. (2015). Effect of Extra Curricular Activity on Student’s Academic Performance. JAFMC Bangladesh, 11 (2). Ahmad, S., Tri, M., & Siti, K.R. (2018). Studi Tentang Prestasi Belajar Siswa Dalam Berbagai Aspek Dan Faktor Yang Mempengaruhi. Jurnal Komunikasi Pendidikan, 2 (2). Arikunto, S. (2010). Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta:Rineka Cipta. Alam Yuli. (2018). Kompetensi Dosen, Motivasi Belajar Mahasiswa dan Dampaknya terhadap Prestasi Mahasiswa dalam Pembelajaran Pengantar Ekonomi (studi pada mahasiswa program studi Manajemen Informatika AMIK Bina Sriwijaya Palembang). Jurnal Manajemen dan Bisnis Sriwijaya, 16 (1).Arni, M. (2007). Komunikasi Organisasi. Jakarta: Bumi Aksara. Basuki & Hariyanto. (2015). Assessment Pembelajaran. Bandung: PT Remaja Rosdakarya. Bertens. (2005). Metode belajar untuk mahasiswa: beberapa petunjuk bagi mahasiswa baru. Jakarta: PT Gramedia Pustaka Utama. Saepuloh. (2017). Pengaruh Keaktifan Mahasiswa Dalam Organisasi Terhadap Prestasi Mahasiswa Di Fkip Universitas Islam Syekh-Yusuf Tangerang. JIPIS, 25 (2). Cahyandaru. (2013). Pengaruh Keaktifan Siswa dalam Ekstrakurikuler terhadap Prestasi Belajar Siswa Kelas XI MAN Yogyakarta II. Skripsi. Universitas negeri Yogyakarta, Yogyakarta. Darmawati Joenita. (2013). Pengaruh Motivasi Belajar Dan Gaya Belajar Terhadap Prestasi Belajar Ekonomi Siswa Sma Negeri Di Kota Tuban. Jurnal Ekonomi Pendidikan dan Kewirausahaan, 1 (1).Dimyati & Mudjiono. (2006). Belajar dan Pembelajaran. Jakarta: Rineka Cipta.  Opit, H. V. (2014). Motivation and Activity Analysis for Improving Learning Achievement of Teaching Planning in State University of Manado. International Journal of Education and Research, 2 (10). Fazzlurrahman., Wijayati., & Witjaksono. (2018). A Measurement of Performance: Student Involvement in Organization and Campus Environment. International Journal of Educational Research Review, 3(4), 11-22. Ferdinand. (2006). Metode Penelitian Manjemen. Semarang: Badan Penerbit Universitas Diponegoro. Ghozali, I. (2016). Aplikasi Analisis Multivariate dengan program IMB SPSS 23. Semarang: BFEE Univeritas Diponogoro. Hamdani. (2011). Strategi Belajar Mengajar. Bandung: Pustaka Setia. Hamalik, Oemar. (2004). Proses Belajar Mengajar. Jakarta: PT. Bumi Aksara. Hartaji, D. A. (2012). Motivasi Berprestasi Pada Mahasiswa yang Berkuliah Dengan Jurusan Pilihan Orang Tua (Skripsi strata satu), Univeritas Gunadarma. Haryono, E., & Akhdinirwanto, W. (2014). Pengaruh Keaktifan Berorganisasi dan Konsep Diri tehadap Indeks Prestasi Mahasiswa Program Studi Pendidikan Fisika Universitas Muhammadiyah Purworejo Tahun Akdemik 2013 / 2014, 4(1), 77– 80. Sohilait., Manopo., & Memah. (2019). Hubungan Keaktifan Berorganisasi Dan Motivasi Belajar Dengan Prestasi Belajar Mahasiswa Angkatan 2016 Fakultas Kedokteran Universitas Sam Ratulangi. Jurnal Medik dan Rehabilitasi, 1 (3). Jihad &  Haris. (2008). Evaluasi Pembelajaran. Yogyakarta: Multi Presindo. Lubis, P. K. D. (2017). Pengaruh Motivasi Belajar Terhadap Prestasi (Studi Kasus Tentang Pembelajaran Mandiri Mata Kuliah Matematika Ekonomi dan Bisnis. Jurnal Niagawan, 6 (2). Pratini, Siti. (2005). Psikologi Pendidikan. Yogyakarta: Studing Pradayu Mahmudi. (2017). Pengaruh Aktivitas Organisasi Terhadap Prestasi Belajar (Studi Kasus Pengurus BEM Universitas Riau Kabinet Inspirasi Periode 2016-2017). Jom Fisip,4 (2).  Pratiwi, S. S. (2017). Pengaruh Keaktifan Mahasiswa Dalam Organisasi Dan Motivasi Belajar Terhadap Prestasi Belajar Mahasiswa Fakultas Ekonomi Universitas Negeri Yogyakarta. Jurnal Pendidikan dan Ekonomi, 6 (1). Priyatno, Duwi. (2014). SPSS 22 Pengelolaan Data Terpraktis. Yogyakarta: CV. Andi Offset Riswanto, A., & Aryani, S. (2017). Learning Motivation And Student Achievement: Description Analysis And Relationships Both. The International Journal of Counseling and Education, 2 (1). Raharjo. (2013) Teori-teori Pembangunan Ekonomi Pertumbuhan. Yogyakarta: Graha Ilmu. Malayu. (2016). Perilaku Organisasi. Jakarta: Bumi Aksara. Manullang. (2008). Dasar-Dasar Manajemen. Yogyakarta: UGM Press. Mediawati. (2010). Pengaruh Motivasi Belajar Mahasiswa Dan Kompetensi Dosen Terhadap Prestasi Belajar. Jurnal Pendidikan Ekonomi Dinamika Pendidikan, 5 (2), 134-146. Sabuj, I. M., Datta, R.K., & Rafiq, N. (2018). The effect of extracurricular activities on the academic performance of the university students: Evidence from Hajee Mohammad Danesh Science and Technology University (HSTU), Dinajpur, Bangladesh. International Journal of Science and Business, 2 (3). Sardiman. (2008). Interaksi dan Motivasi Belajar Mengajar. Jakarta: Grafindo Persada. Saleh, Minhayati. (2014). Pengaruh motivasi, faktor keluarga, lingkungan kampus dan aktif berorganisasi terhadap prestasi akademik.  Jurnal Pendidikan MIPA, 4 (2). Sanjaya. (2008). Strategi Pembelajaran Berorientasi Standar Proses Pendidikan. Jakarta: Prenada Media. Sekaran, U. (2006). Metodologi Penelitian untuk Bisnis, Edisi 4. Jakarta: Salemba Empat.Saepuloh, D. (2017). Pengaruh Keaktifan Mahasiswa Dalam Organisasi Terhadap Prestasi Mahasiswa Di Fkip Universitas Islam Syekh-Yusuf Tangerang. JIPIS, 25 (2). Sholikhah Alfiatus. (2018). Pengaruh Keaktifan Mahasiswa Dalam Organisasi Terhadap Prestasi Belajar Mahasiswa Jurusan Pendidikan Ekonomi Fe Unesa Angkatan 2015. JUPE, 6 (2), 76-80. Siswanto. (2007). Pengantar Manajemen. Jakarta: Bumi Aksara. Siswoyo, Dwi. (2007). Ilmu Pendidikan. Yogyakarta: UNY Press. Sugihartono dkk. (2012). Psikologi Pendidikan. Yogyakarta: UNY Press. Sugiyono. (2016). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta. Sukirman. (2004). Tuntunan belajar di perguruan tinggi. Jakarta: Pelangi Cendekia. Suryabrata. (2007). Psikologi Pendidikan. Jakarta: Raja Grafindo Persada. Sunyato, A. & Rahmad. (2008). Korelasi Antara Keaktifan Dalam Organisasi Kemahasiswaan Dengan Prestasi Belajar Mahasiswa. Jurnal Pendidikan Teknik Mesin, 8 (1). Suprijono. (2009). Psikologi Pengajaran. Yogyakarta: Pustaka Belajar. Sutarto. (2006). Dasar-Dasar Organisasi. Yogyakarta: Gadjah Mada University Press. Slameto. (2015). Belajar dan Faktor-Faktor yang Mempengaruhinya. Jakarta: Rineka Cipta. Syah, Muhibbin. 2003. Psikologi belajar. Jakarta: PT Raja Grafindo Persada. Winardi. (2011). Teori organisasi dan pengorganisasian. Jakarta: PT RajaGrafindo Persada. Winkel, W.S. Psikologi Pengajaran. (Jakarta: Grasindo. 2012). Yuntiwa & Listyo. (2015). Pengaruh Motivasi Belajar Terhadap Prestasi Belajar Mahasiswa Telkom University Program Pendidikan Jarak Jauh Tahun Akademik 2013/2014 (Studi Kasus Pada Program Pasca Sarjana). e-Proceeding of Management, 2 (1). Yulianto, A. (2015). Pengaruh Keaktifan Siswa Berorganisasi Terhadap Peningkatan Soft Skills Dan Prestasi Belajar Siswa Smk Muhammadiyah Prambanan. Jurnal Pendidikan Teknik Mesin, 3 (5).